Nitrosospira sp. Govern Nitrous Oxide Emissions in a Tropical Soil Amended With Residues of Bioenergy Crop - Lourenço, Késia S.; Cassman, Noriko A.; Pijl, Agata S.; van Veen, Johannes A.; Cantarella, Heitor; Kuramae, Eiko E. (Frontiers in Microbiology, 2018)
Organic vinasse, a residue produced during bioethanol production, increases nitrous oxide (N2O) emissions when applied with inorganic nitrogen (N) fertilizer in soil. The present study investigated the role of the ammonia-oxidizing bacteria (AOB) community on the N2O emissions in soils amended with organic vinasse (CV: concentrated and V: non-concentrated) plus inorganic N fertilizer. Soil samples and N2O emissions were evaluated at 11, 19 and 45 days after fertilizer application, and the bacterial and archaea gene (amoA) encoding the ammonia monooxygenase enzyme, bacterial denitrifier (nirK, nirS and nosZ) genes and total bacteria were quantified by real time PCR. We also employed a deep amoA amplicon sequencing approach to evaluate the effect of treatment on the community structure and diversity of the soil AOB community. Both vinasse types applied with inorganic N application increased the total N2O emissions and the abundance of AOB. Nitrosospira sp. was the dominant AOB in the soil and was correlated with N2O emissions. However, the diversity and the community structure of AOB did not changed with vinasse and inorganic N fertilizer amendment. The results highlight the importance of residues and fertilizer management in sustainable agriculture and can be used as a reference and an input tool to determine good management practices for organic fertilization.